Flume tank evaluation of the hydrodynamic lift and drag of helix ropes compared to conventional ropes used in midwater trawls. (1st January 2020) - Kebede, Gebremeskel Eshetu; Winger, Paul D.; DeLouche, Harold; Legge, George; Cheng, Zhaohai; Kelly, David; Einarsson, Haraldur
Abstract: The hydrodynamic properties of ropes can significantly affect the underwater performance of midwater trawls, including their geometry, drag, fuel consumption, and rate of gear setting and hauling activities. In this study, we investigate the hydrodynamic properties of helix ropes compared to conventional polyethylene (PE) and nylon (PA) ropes. Flume tank tests were conducted using 17 different braided and twisted ropes of varying diameter (6 mm, 8 mm, 9 mm, and 14 mm). Samples of each rope type were subjected to a series of water velocities (0.5 m/s, 0.7 m/s, and 0.9 m/s) and angles of attack (0°, 12°, 20°, 45°, 61°, and 90°) in order to measure drag and lift forces. To understand how hydrodynamic coefficients vary with increasing Reynolds number (Re), we also evaluated a wider range of water velocities (0.3 m/s to 0.9 m/s) for 14 mm ropes. Our results showed that, when compared to conventional ropes of the same diameter, helix ropes produced increased lift force ( L ), verifying their description as self-spreading ropes. To our knowledge, these findings represent the first known evidence of its kind published in scientific literature with direct application to midwater trawling operations. Highlights: Helix ropesfor Midwater trawl are unique of containing helical ropes wrapped over core strand in S and Z lays . Hydrodynamics of helix ropes and conventional ropes investigated using Flume Tank tests at flow speeds of 0.5 m/s 0.9 m/s. Effects of Reynolds number on the hydrodynamic force coefficients were studied for 14 mm rope samples. Helix ropes produced increased lift relative to conventional ropes, and are verified to be called self-spreading ropes.